Studi Perbandingan Konsep Barat dan Islam Mengenai Gratitude dan Rasa Syukur - Sri Wulandari (Jurnal Psikologi Terapan, 2018)
Gratitude in the western perspective is an expression of gratitude by the individual for all the good things he receives, be they objects, a happy life, can handle the difficulties experienced. The notion of gratitude is not far from the perspective of gratitude in Islam. Gratitude in the perspective of Islam is an activity that Muslims do as a form of gratitude for all the blessings given by God, such as spiritual favors, physical favor, favors of faith and, also favors of Islam. But among the gratitude of the western perspective with gratitude in the perspective of Islam there are some differences. Where gratitude in the western perspective is defined as a form of gratitude for kindness and reflection of the good through feeling, sharing, and a positive attitude to help others and reciprocate the good of others. While gratitude in the perspective of Islam, more reflect on the value of goodness received by the granting of Allah Subhanahu wa Ta'ala.